Mental Health Evaluation and Assistance for Visually Impaired People - Pandey, Kavita; Pandey, Dhiraj (EAI Endorsed Transactions on Scalable Information Systems, 2023)
Earlier, three-person out of every 10 persons had been suffering from mental health issues but nowadays this situation became worsened due to the pandemic. The number of individuals suffering from mental health has been increasing day by day. One of the WHO reports states that 3.8% of the population has been affected due to depression. Although such an important issue in human health, still it is one of the neglected health sectors around the world. This situation is more worsened among special need people as they feel more anxiety disorders and loneliness in comparison to their sighted peers. Technology is helping us to solve several such problems which are difficult to discuss with peers and worsen over time if not taken preventively on time. In this article, a technological solution using facial expression and voice-based assistance has been used. This would especially help in monitoring the mood of visually challenged people.  Their mental health can be monitored and assistance would be provided as per the severity of the situation. Mental health is analyzed based on emotion recognition from facial expressions and psychometric evaluations. A health score would be calculated which is used to judge the severity of mental health. An assessment report would also be generated and sent to the guardian of the user. The whole application is designed with a voice assistance platform using Dart (Flutter) and firebase as storage for all interactions with the visually challenged person.
Keywords: Mental Health; visually impaired; monitoring and assistance; depression